Analysis of Ecotourism Development and Sustainability in The Heart of Borneo, Indonesia - Risty Chrismansyah (Program Studi Pariwisata Fakultas Ilmu Budaya Universitas Gadjah Mada Yogyakarta, 2022)
This research critically evaluates the current planning and implementation of ecotourism development in the Indonesian part of the Heart of Borneo. In 2012, President Susilo Bambang Yudhoyono declared that Indonesia would pay more attention to forest preservation rather than exploitation. However, anthropogenic activities continue damaging the Heart of Borneo. Ecotourism development is viewed as a solution to mitigate the area’s environmental and socio-economic issues; however, development remains in the planning phase. Thus, this research aims to evaluate the planning of ecotourism in the Heart of Borneo and the extent development aligns with ‘best practice’. Taking a constructionist approach that utilised secondary document analysis, this research analysed 36 documents published by several non-governmental and governmental institutions, academic journals and online media in Indonesia. Several gaps were identified between the socio-environmental policies and the rhetoric produced by the government and ministries, highlighting an inconsistency on the governmental level in conducting sustainable tourism development. Local involvement also needs to be improved through partnerships to achieve the Heart of Borneo’s ecotourism development goals.